Kaedah unsur terhingga menggunakan kaedah lelaran kumpulan tak tersirat bagi masalah resapan satu matra - Jumat Sulaiman; Abdul Rahman Abdullah (2011)
Previous studies on the block iterative method focus mainly on the finite difference method. This paper presents the formulation and application of the 2, 3 and 4 point Explicit Group (EG) iterative methods scheme on the finite element approximation equation to solve the ine dimensionaldiffusion problems. Finally, one numerical test was implemented to show the computational efficiency of the EG iterative method on the finite element